LEFT MAIN CORONARY ARTERY OCCLUSION: SURGICAL MANAGEMENT - Tector, Alfred J. (1974)
Left main coronary occlusion is a rare lesion. A case that was successfully managed by coronary bypass surgery is presented. Occlusion of the left main coronary artery and management of left main coronary artery disease is discussed.